Case Report: Autistic child with restrictive eating behaviour, limping gait and erythematous gingival mass-scurvy? - Logonathan, Preeyanikaa; Muhd Noor, Nurhidayah; Marsom, Aminah (Frontiers in Child and Adolescent Psychiatry, 2025)
Scurvy, a condition caused by a deficiency in ascorbic acid, is often considered an outdated, textbook disease, largely forgotten in the 21st century. However, recent reports indicate a rise in cases, particularly among individuals with risk factors for nutritional deficiencies or those with specific dietary habits. These cases are frequently misdiagnosed, leading to a series of unnecessary tests that could be avoided with a thorough assessment of dietary intake. In this report, we present the case of a 10-year-old with autism spectrum disorder (ASD) and a selective eating pattern, who presented with a limping gait, tenderness in the right calf, and significant weight loss. A skin examination revealed multiple perifollicular hemorrhages with corkscrew-shaped hair, as well as localized erythematous and hypertrophic gingiva in all four quadrants. Based on clinical findings, scurvy was suspected, and vitamin C supplementation was initiated both for diagnostic and therapeutic purposes. The diagnosis was confirmed when serum vitamin C levels were found to be critically low (5 µmol/L, normal range: 28–120 µmol/L). The patient's response to vitamin C was impressive, with complete gingival healing and noticeable weight gain within three weeks. Although scurvy is often thought of as an ancient disease, it has seen a resurgence, posing diagnostic challenges due to its diverse clinical manifestations. Early diagnosis, along with appropriate intervention and dietary changes, can lead to an excellent prognosis for individuals with scurvy.